Socio-Economic Consequences of Agricultural Land Use Change in Tarai of Nawalparasi District - Dhakal, Bhola Nath (The Third Pole: Journal of Geography Education, 2019)
Changes in agricultural land use have a profound impact on the personal, family and social lives of people living in rural as well as semi-urban communities. The main objective of this paper is to explore socio-economic consequences of agricultural land use change during 2005/06 to 2015/16 in Nawalparasi District. This paper is based on collected primary data through household questionnaire survey, Focus Group Discussion (FGD), Key Informant Interview (KII) and field observation methods. Secondary sources of data through published and unpublished government documents, topographic and cadastral maps, and satellite images have been used in this study. Loss of cropping land and decreasing productivity, land fragmentation and increasing cost of inputs, changes in food security, increasing the land value, housing and rental cost, change in occupation, sources of income and expenditure and implementation of intensification and diversification strategies are the major consequences found in the study sites.